Effect of Low Level Laser Therapy (LLLT) on Pain, Trismus and Quality of Life (QOL) in Post Lower Third Molar Removal Patients : A Randomized Controlled Trial - Andi Dala Intan; Nyoman Murdana; SA Nuhonni; Lilies Dwi (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background: Low-Level Laser Therapy (LLLT) is a physical modality used in a rehabilitation support service. Patients with lower third molar impacted experience decline in QOL due to inflamatory response,such as bleeding, swelling, stiffness and pain. This leads to disability in daily activities, such as eating and drinking during several days post removal.Methods: It is a randomized controlled trial (RCT) and single blind study. A total of 21 subjects in LLLT and 21 subjects in control groups with the age range of 18-30 years. Subjects in the study group were given a totaldose of 54 J, energy density 18J/cm2 on day 0, 3 and 7 post lower third molar impacted surgery. Both groups were assessed for QOL values using the Short Form 36 (SF-36) before and after therapy.Result: Decrease in Pain (VAS) and Trismus on the third and seventh day post operatively were statistically significant (p <0.05) between the two groups. QOL improvement on the SF-36 domains of Role Physically(RP), Bodily Pain (BP), General Health (GH) was statistically significant (p <0.05) in both groups. Moreover, QOL improvement in Physical Components (PCS) was also significant between the two groups.Conclusion: LLLT could reduce postoperative pain of lower third molar impacted patients from day 0 to 3 and completely painless on the seventh day postoperatively. LLLT therapy eliminated Trismus on the third dayafter the surgey. Increase QOL in patients with lower third molar impacted removal after LLLT was evident in the physical component. The positive changes in pain and trismus reduction, also QOL improvement postLLLT can restore patients’ activities of daily living as usual in a short period of time.Keywords : Low Level Laser Therapy (LLLT), Pain, Trismus, Quality of Life, Rehabilitation, Lower Third Molar Removal.